Ethnic identity and eating disorders in adolescence and mental health in young adulthood - Niia, Katarina Sofie Holmlund (UiT Norges arktiske universitet, 2021)
Background: How the Sami ethnicity, ethnic factors and ethnic discrimination are related to mental health has been investigated previously. An interesting, and as far as I know until now unexplored topic of research is the relationship between adolescence eating disorders, ethnic factors, and mental health outcome in young adulthood. The aims of the study was to investigate the relationship between ethnicity, ethnic factors, body image in adolescence and having an eating disorder in adolescence. Finally also investigating the relationship between the above mentioned factors and mental health outcomes in young adulthood. Method: Data was collected from the Norwegian Arctic Adolescent Health Study (2003- 2005) and participants were linked to the Norwegian Patient Registry (2008-2012), with 3987 participants. Eating disorders, ethnicity, ethnic factors, and body image in adolescence were based on self-report from the survey and use of mental health care in young adulthood from NPR. Analyses were carried out using independent t-tests, Chi-square test and multivariable regression. Results: There were found no overall differences between Sami and non-Sami in prevalence of eating disorders in adolescence, or use of mental health care in young adulthood. A significant association was found between body image and dieting, and having an eating disorder in adolescence. An association was found between ethnic identity exploration and eating disorders in adolescence among Sami adolescents. No significant relationship was found between ethnic factors, nor eating disorders in adolescence, and use of mental health care in young adulthood. Conclusion: Eating disorders in adolescence and use of mental health care in young adulthood were as common among Sami as non-Sami. Ethnic factors were more pronounced, and had more effect on the outcome of the Sami. Body image was associated with eating disorders. Ethnic factors, nor eating disorders in adolescence was a predictor for use of mental health care in young adulthood.